How to present quality of life outcomes after focal therapy: using validated instruments and novel statistical methods. Issue 3 (23rd May 2022) - Clements, Matthew B.
Abstract : Purpose of review: To provide an up-to-date summary of widely used patient-reported measures for focal therapy quality of life outcomes and review contemporary analytic methods and recommendations for data visualization. Recent findings: Measures such as pad-use, or preferably validated instruments such as the International Consultation on Incontinence Questionnaire, MSKCC Prostate Quality of Life Survey, or Expanded Prostate Cancer Index (EPIC) should be used for urinary function assessment. Sexual Function can be assessed with the International Index of Erectile Function or EPIC, but researchers must be careful to account for patients that are not currently sexually active when analyzing outcomes. Measurement of baseline function is crucial for a meaningful understanding of post-treatment outcomes. When multiple measurements are collected, longitudinal models such as generalized estimating equations or linear mixed effects models are preferred. Whenever possible, the data visualization should mirror the hypothesis testing for clarity of interpretation, and use of restricted cubic splines or generalized additive models are preferred to illustrate non-linear trajectories in quality of life after treatment. Summary: Advances in both the measurement of patient quality of life with validated instruments and statistical methods have allowed for a more complete understanding and reporting of outcomes, which can be applied to the evaluation of focal therapy for prostate cancer.